PEMBINAAN PENDIDIKAN DAYAH MELALUI KEGIATAN PELATIHANLIFE SKILL SANTRIWAN DAN SANTRIWATI KABUPATEN ACEH TENGAH - Kausara Usman (CV. ADIBA AISHA AMIRA, 2023)
Dayah is the oldest Islamic educational institution in Indonesia, allegedly as an education system that was born and grew through Indonesian culture that is